Blackhorse riders [compact disc, unabridged] : a desperate last stand, an extraordinary rescue mission, and the Vietnam battle America forgot - Keith, Phil. 1946- (Tantor Media, 2012)
The incredible true story of a brave military unit in Vietnam that risked everything to rescue an outnumbered troop under heavy fire, and the thirty-nine-year odyssey to recognize their bravery.